Predictors of Protean Career for Millennial Workers: The Impact on Career Resilience and Career Satisfaction - Sinto Sunaryo; Risgiyanti Risgiyanti; Joko Suyono (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2023)
A contemporary career model, the protean career has offered an alternative for career development in the workplace, especially for the millennials. This study aims to analyze the core self-evaluation and emotional intelligence as the predictors of protean career and the impacts on career resilience and career satisfaction. Online survey from 260 millennials who work in various industries were analyzed to develop an integrative career model, by using partial least square structural equation modelling (PLS-SEM). The results of the study indicated core self-evaluation and emotional intelligence as predictors that have a significant effect on protean careers. In addition, the research found the significant effect of protean career on career resilience, also the significant effect of career resilience on career satisfaction. This study contributes to the development of career literature through a contemporary approach that emphasizes the individual role in career development. This study also provides managerial implications, where managers need to consider emotional intelligence in the recruitment process and encourage employees’ ability to evaluate themselves for career success. Keywords: Core self-evaluation, emotional intelligence, protean career, career resilience, career satisfaction